1993
DOI: 10.1177/00220345930720011201
|View full text |Cite
|
Sign up to set email alerts
|

A Quantitative Study of Calcium Binding and Aggregation in Selected Oral Bacteria

Abstract: By means of micro-equilibrium dialysis, calcium binding capacities and affinities were measured in three different oral bacteria, and the effects of extracellular polysaccharide, pH, and aggregation were investigated. Binding capacities of 31.0 +/- 2.1 (C. matruchotii), 34.7 +/- 3.7 (S. sanguis), and 41.5 +/- 5.4 (S. downei) mumol calcium/g wet weight of cells were found at pH 7.0, falling to 21.4 +/- 0.8 mumol calcium/g wet wt. cells at pH 5.0 for S. downei. Dissociation constants were found to vary between 0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
54
1
15

Year Published

1993
1993
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(73 citation statements)
references
References 20 publications
3
54
1
15
Order By: Relevance
“…2 Also, the lower protein concentration in bacterial pellets (Table 1) is in agreement with van Houte et al, 8 who reported decreased bacterial cell density when this S. mutans strain was grown in THB supplemented with 2% sucrose as compared to the same medium with a ten times lower concentration. Considering that proteins from bacterial cell walls are Ca-binding sites, 20 and EPS does not have this property, 9 it would be expected that bacterial pellets grown in the presence of sucrose would have a lower ability to bind Ca per weight of bacteria. Although this was observed for the baseline Ca concentration in the bacterial pellets (Table 1), the results of Ca binding after treatment with Ca-containing solutions did not support this hypothesis (Figure 1), and the theoretical support to explain these results is presented below.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…2 Also, the lower protein concentration in bacterial pellets (Table 1) is in agreement with van Houte et al, 8 who reported decreased bacterial cell density when this S. mutans strain was grown in THB supplemented with 2% sucrose as compared to the same medium with a ten times lower concentration. Considering that proteins from bacterial cell walls are Ca-binding sites, 20 and EPS does not have this property, 9 it would be expected that bacterial pellets grown in the presence of sucrose would have a lower ability to bind Ca per weight of bacteria. Although this was observed for the baseline Ca concentration in the bacterial pellets (Table 1), the results of Ca binding after treatment with Ca-containing solutions did not support this hypothesis (Figure 1), and the theoretical support to explain these results is presented below.…”
Section: Discussionmentioning
confidence: 99%
“…In order to remove remnants of culture broth and unbound Ca, the pellets were sequentially washed using sonication (Vibra Cell sonicator, Sonics and Materials, Danbury, USA) at 7 W for 1 min, first in 0.05 M PIPES buffer, pH 7.0, followed by 0.01 M EDTA solution, and again in PIPES buffer. 9 Between each washing, the pellet was recovered by centrifugation. After this procedure, the pellet was spread on filter paper to remove excess moisture.…”
Section: Bacterial Preparationmentioning
confidence: 99%
See 2 more Smart Citations
“…Since Ca 2+ was first studied in bacteria fifty years ago (Norris & Jensen, 1957) it has been implicated in a broad range of physiological processes in prokaryotes that include chemotaxis and motility (Tisa & Adler, 1992Watkins et al, 1995;Pitta et al, 1997), pathogenesis (Rose et al, 1993;Straley et al, 1993), the cell cycle and the control of the initiation of replication (Jiménez-Sanchez et al, 1993;Yu & Margolin, 1997), quorum sensing (Wherten & Lundgren, 2001) and spore and fruiting body formation (Inouye et al, 1983;O'Hara & Hageman, 1990). In many cases, the involvement of Ca 2+ in the regulation of cellular processes has been roughly described in terms of an influx or efflux of Ca 2+ from the cytosol.…”
Section: Introductionmentioning
confidence: 99%